P235 Epigenetic landscape of the asthmatic airways. (15th November 2016) - McErlean, P; Kelly, A; Dhariwal, J; Watson, J; Jurdzinski, N; Smith, J; Solari, R; Edwards, MR; Oosterhout, A Van; Johnston, SL; Lavender, P
Abstract : The airway epithelium of asthmatics exhibits distinct genomic and phenotypic characteristics. However the mechanisms underlying the establishment and chronicity of these characteristics remains unknown. We investigated if epigenetic changes underpin the genomic characteristics of the asthmatic airways by determining the chromatin landscape of bronchial epithelial cells (BECs) in healthy and asthmatic adults. We employed ChIP-seq of histone H3 acetylation (H3K27ac) to determine the chromatin landscape in e x vivo cultured BECs from healthy and allergic-atopic asthmatics (n = 3 donors each). Regions of differential enrichment were identified (MEDIPS) and associated genes and pathways determined (GREAT). Gene expression profiles were investigated by microarray (Illumina) and differential analysis conducted (Partek Genome Suite). Super enhancers (SEs) were identified (ROSE) and enrichment of transcription factor motifs (MEME) and their tissue distribution (protienatlas.org) determined. We identified 33, 744 differentially enriched regions (DERs) of H3K27ac between asthma and healthy BECs. DERs were associated with genes (e.g. SERPINB2, TSLP) and pathways (e.g. leukotriene synthesis, antiviral response) previously implicated in asthma and had little overlap with known glucocorticoid receptor binding sites (1.7% of total). DERs occurred up to 100kb from gene promoters and gain or loss of H3K27ac was associated with increased and decreased gene expression in asthmatics respectively. Using a comparative approach, we identified SEs that were common (i.e., present across all donors) and distinct to health and asthma. In addition to established asthma genes (e.g. CLCA1) and transcription factors (e.g. TP63), asthma-SEs encompassed non-coding RNAs (up to 32% of genes) and epithelial-specific transcription factors (e.g. GCM2) previously unreported in asthma. Our data indicates that asthma influences the chromatin landscape of BECs and suggests the genomic differences observed in the asthmatic airway epithelium are underpinned by established epigenetic mechanisms.